Интеллектуальное управление: подходы, результаты и перспективы развития - Павлов, В.В.; Шепетуха, Ю.М.; Мельников, С.В.; Волков, А.Е. (Кибернетика и вычислительная техника, 2017)
Рассмотрены текущее состояние и перспективы будущего развития нового научного направления — интеллектуального управления. Среди основных теоретических и прикладных результатов в данной предметной области можно указать разработку технологий и алгоритмов управления скоростными динамическими процессами в распределённой компьютерной среде, структуризацию моделей формирования хаотического поведения системы, создание методов улучшения качества обмена данными между компонентами сетецентрической системы. Розглянуто поточний стан та перспективи майбутнього розвитку нового наукового напрямку — інтелектуального управління. Серед головних теоретичних та прикладних результатів у цій предметній галузі можна зазначити розробку технологій та алгоритмів керування швидкісними динамічними процесами у розподіленому комп’ютерному середовищі, структуризацію моделей формування хаотичної поведінки системи, створення методів поліпшення якості обміну даними між компонентами мережецентричної системи. The purpose of the paper is to examine existing approaches, current state, important results and prospects for future development of such new scientific direction as intelligent control. Results. One may stress two main directions in the field of intelligent control where promising results have been achieved. The first one, related to the creation of intelligent infrastructure, includes development of methods and structures of distributed control as well as examination of non-linear applied processes in objects with variable properties. The second direction, attributed to the creation of intelligent agents, includes elaboration of methods, models and algorithms for real-time decisions related to the efficient control of dynamic objects.